2008
DOI: 10.1111/j.1945-5100.2008.tb00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Wild 2 particles to chondrites and IDPs

Abstract: Comparing Wild 2 particles to chondrites and IDPs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(153 citation statements)
references
References 45 publications
8
143
2
Order By: Relevance
“…Our spectral decomposition results suggest that the crystalline olivine grains in the inner belt contain more Fe than is expected for comet-like bodies (Wooden 2008;Zolensky et al 2008;Hanner & Zolensky 2010). Similar results were also found for cold crystalline olivine grains observed in other debris disks (β Pic, de Vries et al 2012), and protoplanetary disks (e.g., Olofsson et al 2010;Sturm et al 2010Sturm et al , 2013.…”
Section: The Origin Of Transient Dustsupporting
confidence: 75%
“…Our spectral decomposition results suggest that the crystalline olivine grains in the inner belt contain more Fe than is expected for comet-like bodies (Wooden 2008;Zolensky et al 2008;Hanner & Zolensky 2010). Similar results were also found for cold crystalline olivine grains observed in other debris disks (β Pic, de Vries et al 2012), and protoplanetary disks (e.g., Olofsson et al 2010;Sturm et al 2010Sturm et al , 2013.…”
Section: The Origin Of Transient Dustsupporting
confidence: 75%
“…Microchondrule-like objects with textural, mineralogical and isotopic properties of chondrules in carbonaceous chondrites have also recently been found in Wild 2 samples . Their presence as well as that of a CAI in the Stardust samples has been attributed to a large scale mixing of high-temperature minerals formed in the inner solar system Nakamura et al, 2008;Simon et al, 2008).…”
Section: Anhydrous Idpsmentioning
confidence: 99%
“…For both comets, the mineralogical findings echo the results from the Stardust mission on comet P81/Wild 2. Based on samples collected in situ, Zolensky et al (2008) found that olivines in the comet mostly consist of Mg-rich olivine grains, with a Mg fraction (=Mg / [Mg + Fe]) of about 99. However, they also found the composition range of olivine to be extremely broad, ranging from Mg fractions between 4 and 100.…”
Section: Cometary Bodiesmentioning
confidence: 99%